Delta ferrite formation and evolution during slab processing from an 80-ton industrial heat of AISI 304 austenitic stainless steel - Santos,Flávia Andressa Moreira dos (2023)
Abstract Although delta ferrite is a very common phase in most austenitic stainless steels, studies about its formation and evolution during slab processing from industrial heats of tens of tons are scarce. The main objective of this research is to study the evolution of delta ferrite (quantity, chemical composition, morphology, and distribution) along the production route from the cast slab to the coil of an industrial heat of 80 tons of 304 stainless steel. Samples were extracted after the following processing steps: continuous casting, first and second hot-rolling pass, and solution-heat-treating, arriving at the final commercial condition. Sample analyses were carried out with several complementary microstructural characterization techniques: optical microscopy, scanning electron microscopy with energy dispersive spectroscopy (EDS), X-ray diffraction, and magnetic measurements of delta ferrite content (feritscope). Thermocalc® indicates that the present continuous cast slab solidifes according to the FA (ferrite-austenite) mode and the final microstructure should be completely austenitic in equilibrium conditions. Nevertheless, delta ferrite is detected along the processing steps, indicating that the steel is out of phase equilibrium. The ferrite content measured after solidification varies significantly across the as-cast slab thickness. Lower values are detected on the surfaces, followed by a gradual increase when moving into the slab, reaching a peak, and finally decreasing at the slab center. This pattern of delta ferrite content is named “M type” distribution. The average content of delta ferrite decreases after each subsequent processing step, namely the two hot-rolling passes and the solution heat-treating.